2010
DOI: 10.1016/s1413-8670(10)70083-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antimicrobial susceptibility of respiratory pathogens in patients with cystic fibrosis

Abstract: Respiratory infection is very common in patients suffering from cystic fibrosis (CF). However, the antimicrobial resistance rate of isolates from CF patients is not often documented. In this study, 279 respiratory specimens of 146 patients were prospectively collected from July to December 2006. Microbiological cultures and antimicrobial susceptibility tests of the most frequently isolated bacteria were performed. Sputum and oropharyngeal swabs were processed for culture. During the study period, 50% of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
10
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
5
10
2
2
Order By: Relevance
“…We isolated P. aeruginosa, K. zaenae, A. xylosoxidans, A. denitrificans, K. pneumoniae, S. maltophilia, E. hermannii, E. agglomerans, E. cloacae, E. kobei and C. koseri. As reported by Paixão et al, in 2010, P. aeruginosa as is the most frequent pathogen in CF patients [39]. We obtained the same result.…”
Section: Discussionsupporting
confidence: 91%
“…We isolated P. aeruginosa, K. zaenae, A. xylosoxidans, A. denitrificans, K. pneumoniae, S. maltophilia, E. hermannii, E. agglomerans, E. cloacae, E. kobei and C. koseri. As reported by Paixão et al, in 2010, P. aeruginosa as is the most frequent pathogen in CF patients [39]. We obtained the same result.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, we found an MBL gene (bla SPM-1 ) in only one carbapenem-resistant CF isolate. Reports of MBL among CF P. aeruginosa are sparse but indicate a low prevalence of these carbapenemases (18,19). This supports the view that carbapenem resistance mechanisms in CF P. aeruginosa are not solely due to widespread metallo beta-lactamases.…”
Section: Discussionmentioning
confidence: 59%
“…Colonization by pathogenic bacteria, especially P. aeruginosa, in the respiratory tract occurs at a young age in patients with CF and represents a major health problem because it is considered a serious cause of mortality and morbidity. A previous study of the prevalence and antibacterial susceptibility of bacterial isolates from CF patients in Germany, the U.S., and South America reported that P. aeruginosa isolates were the most frequent pathogens of CF patients (9). The educational level of mothers of CF children and family awareness were reported to play important roles in the spread of infection with P. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%